EFFECT OF CORE STABILITY EXERCISES BY USING SWISS BALL ON BALANCE AND CORE MUSCLE STRENGTH IN CHILDREN WITH DOWN SYNDROME - Shah, Dr Vidhi; Anuj Lahoti; palekar, Tushar J; Chanageri, Shradha; Chitale, Neha; Amrohi, Nazia Lateef (Journal of Neonatal Surgery, 2025)
Background: Children with Down syndrome experience significant motor and balance impairments due to hypotonia, muscle weakness, and structural brain differences, limiting their ability to perform daily activities. Core stability exercises are known to enhance postural control and functional mobility, but there is limited research exploring their effects using a Swiss ball in this population. Objectives: This study aimed to evaluate the effect of core stability exercises using a Swiss ball on balance and core muscle strength in children with Down syndrome. Methodology: Thirty children aged 8–12 years with Pediatric Balance Scale scores between 21 and 40 were included in the study. Participants underwent 15 sessions of core stability exercises using a Swiss ball, with pre and post intervention assessments of dynamic balance (Timed Up and Go Test), static balance (Standing Stork Test), and core strength (Pressure Biofeedback Unit). Statistical analysis was conducted using paired t-tests and Wilcoxon Signed Rank tests, with significance set at p < 0.05. Results: Significant improvements were observed across all outcome measures post-intervention. The Timed Up and Go Test scores improved from 15.62 ± 3.726 seconds to 12.97 ± 3.590 seconds (p < 0.01). Standing Stork Test scores increased from 2.07 ± 1.067 seconds to 3.17 ± 1.256 seconds (p < 0.01). Pressure Biofeedback scores improved from 1.17 ± 1.037 units to 2.24 ± 0.988 units (p < 0.01). Conclusion: The findings of present study support the inclusion of Swiss ball exercises in physiotherapy programs to enhance functional mobility and reduce the risk of falls in the children with Down Syndrome.